An Analysis of Optimal Command Guidance vs. Optimal Semi-Active Homing Missile Guidance - Nesline, F. William; Nesline, Mark L. (1986 American Control Conference, 1986)
An optimal command guidance system and an optimal semi-active homing missile guidance system are analyzed using adjoint theory. Both systems contain a Kalman filter to estimate the states and an optimal full state guidance law to generate the acceleration commands. The dynamics and error inputs of both systems are presented. Required accelerations and terminal miss distance are the performance measures used to evaluate the systems at short and long range intercept conditions. For short range intercepts, command guidance measurement noise is always less than that for semi-active guidance if a large tracking radar is used. Performance is essentially equivalent for the two systems, however, because semi-active homing noise decreases as the target to missile range gets smaller. For long range intercepts semi-active homing performance is much better. This is because the semiactive guidance measurement noise becomes smaller than the relatively constant command guidance measurement noise. Cost factors involved in each type of system are discussed.